The expression of certainty and uncertainty with complex structures based on the Kabardian-Circassian, Russian and English languages - Rita B. Kenetova; Alberd T. Boziev; Zagirat T. Khashozheva (Кавказология)
In this article, the authors consider the category of certainty/uncertainty in differently structured languages using the example of Kabardino-Circassian, Russian and English, and also highlight the reasons why the absence of articles in Russian and Kabardino-Circassian languages causes difficulties for native speakers of these languages when learning English. Articles in English carry a significant burden: they help clarify the meaning of nouns, indicating their number, specificity or universality. The conducted research allows us to conclude that the category of certainty/uncertainty is represented in the three languages studied, however, the ways of expressing this category differ. In Kabardino-Circassian, it is expressed morphologically by means of formants, in English by means of the official part of speech, and in Russian by lexical means of expression.